The Effect of Orphenadrine on Rewarding Property of Morphine-Induced Conditioned Place Preference - Köse, Çağla; Shahzadi, Andleeb; Akkan, A. Gökhan; Özyazgan, Sibel (Cerrahpaşa Medical Journal, 2020)
Objective: Orphenadrine (Orp), an anti-cholinergic drug, is subjected to drug abuse and dependence in recent years. This experiment was designed to study the effect of Orp on rewarding and reinforcing properties of morphine-induced conditioned place preference (CPP). Methods: Rats were randomly divided into six groups as control (serum physiological), morphine (10 mg/kg), Orp (20 mg/kg and 30 mg/kg), and Orp + morphine (20 mg/kg, 30 + 10 mg/kg, respectively). After pretest, the rats were given multiple intraperitoneal injections of saline solution and Orp on alternative days. Results: Morphine significantly enhanced the preference scores in the drug-paired side (p<0.001), whereas both groups with doses of Orp (20 mg/kg and 30 mg/kg) did not exhibit any preference compared with the control group. Orp (30 mg/kg) + morphine showed no preference, whereas Orp (20 mg/kg) + morphine significantly decreased the CPP when compared with morphine group (p<0.01). The combined used of Orp (20 mg/kg) + morphine reduced the preference, whereas Orp (30 mg/kg) + morphine did not exhibit acquisition of CPP in rats. Conclusion: The acquisition of CPP is thought to be due to N-methyl D-aspartate receptor antagonistic effects of Orp at low dose. It is thought that the rewarding feature or abuse potential should be analyzed in further investigation. Cite this article as: Köse Ç, Shahzadi A, Akkan AG, Özyazgan S. The Effect of Orphenadrine on Rewarding Property of Morphine-Induced Conditioned Place Preference. Cerrahpaşa Medical Journal 2020; 44(2): 80-85.